2019
DOI: 10.1142/s0218213019600017
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Learning Methods in Classifying Organized Behavior in Tweet Collections

Abstract: The successful use of social media to manipulate public opinion via bots and hired individuals to spread (mis)information to unsuspecting users reached alarming levels due to the manipulations during the 2016 US elections and the Brexit deliberations in the UK. Fake interaction such as “liking” and “retweeting” are staged to foster trust in the posts of bots and individuals, which makes it difficult for individuals to detect the posts that are part of greater schemes. We propose an approach based on supervised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…According to [8], any biased message, intentional or unintentional, can be termed propaganda. The social ramifications of propaganda are manifold, ranging from the manipulation of elections [9,10] to health [11]. It is also observed that the propaganda phenomenon is not limited to specific demographic regions or languages.…”
Section: Introductionmentioning
confidence: 99%
“…According to [8], any biased message, intentional or unintentional, can be termed propaganda. The social ramifications of propaganda are manifold, ranging from the manipulation of elections [9,10] to health [11]. It is also observed that the propaganda phenomenon is not limited to specific demographic regions or languages.…”
Section: Introductionmentioning
confidence: 99%